DEVELOPMENT AND VALIDATION OF HPTLC METHOD FOR DETERMINATION APIXABAN IN BULK AND TABLETS - Jain, Hemant K.; Nikam, Vishal K. (International Journal of Applied Pharmaceutics, 2017)
Objective: To develop a simple and sensitive, high-performance thin layer chromatographic (HPTLC) method for the quantitative estimation of apixaban in bulk and tablets. Methods: Sample of apixaban was applied on silica gel 60 F254 TLC plates under pure nitrogen stream by linomat TLC applicator. Separation was carried out by using toluene, methanol and diethylamine as a mobile phase in a ratio of 16:3:1 v/v/v. Developed TLC plates were scanned by camag TLC scanner and detection was carried out at 288 nm. Results: Rf value of apixaban was found to be 0.4. The linearity was found from 50 to 350 ng/spot. The mean percentage recovery was found to be 85.66with % RSD of 0.79. Conclusion: The present study represents first HPTLC method that deals with the estimation of apixaban. Validation results indicated that the developed method is simple, rapid, accurate, specific, sensitive and precise. The developed method was validated as per ICH Q2 (R1) guideline by studying various validation parameters like accuracy, precision, specificity, assay, LOD and LOQ. It can be concluded that the method can be used in routine analysis of apixaban in tablet dosage form.